The Influence of Internal Branding and Perceived Supervisor Support on Turnover Intention Mediated by Work Engagement in Nurses at Rsup Dr. Soeradji Tirtonegoro Klaten - Haq, Justika Hanifah; Aseanty, Deasy; Putra, Andreas Wahyu Gunawan (Asian Journal of Management Analytics, 2025)
This study investigates the effect of internal branding and perceived supervisor support on turnover intention, with work engagement as a mediating variable among nurses at RSUP dr. Soeradji Tirtonegoro Klaten. A quantitative approach was used with 120 nurses as respondents. Data were collected via questionnaires and analyzed using descriptive statistics and Structural Equation Modeling (SEM). Results show that internal branding and perceived supervisor support positively affect work engagement. Internal branding indirectly reduces turnover intention through work engagement, while perceived supervisor support does not show a significant indirect effect. These findings highlight the importance of internal branding in enhancing work engagement and reducing turnover intention among nurses.